K-strategic ammonia-oxidizing bacteria capitalize on biological nitrogen fixation in a flooded, unfertilized rice soil - Bei, Qicheng; Xie, Zubin; Cadisch, Georg; Rasche, Frank (Biology and fertility of soils, 2019)
Less attention has been devoted to the understanding of the sequential effect of biological nitrogen fixation (BNF) on microbial ammonia (NH 3 ) oxidation in terrestrial soils. To shed light into this ecologically important relationship, a 15 N 2 -DNA-stable isotope probing (SIP) technique was applied to explore the incorporation of 15 N fixed by BNF into the genome of NH 3 oxidizers in planted and non-planted flooded rice soils, using the α-subunit of NH 3 monooxygenase ( amoA gene) as a functional marker. The abundance and structural composition of archaeal and bacterial amoA genes in density-resolved fractions obtained from SIP were investigated by quantitative PCR, as well as terminal-restriction fragment length polymorphism and sequence analyses. Results revealed that bacterial rather than archaeal NH 3 oxidizers assimilated 15 N derived from BNF in both planted and non-planted flooded rice soils. The amoA genes in 15 N-enriched “heavy” SIP gradient fractions were closely related to K-strategic Nitrosospira cluster 10, including Nitrosospira sp. AF-like bacteria, suggesting an ecological linkage of these two metabolically distinct processes. It remains unsolved from our study why exactly Nitrosospira cluster 10 was capitalizing on BNF. It could be suggested that K-strategy is the underlying ecological mechanism of sustainable, self-regulating terrestrial ecosystems such as traditional, unfertilized flooded rice soils. In this regard, it needs to be assayed if some rice-associated diazotrophs might also be classified as K-strategists, since BNF is an energy demanding metabolic process.